2021
DOI: 10.1101/2021.10.08.463476
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Covert valuation for information sampling and choice

Abstract: We use our eyes to assess the value of objects around us and carefully fixate options that we are about to choose. Neurons in the prefrontal cortex reliably encode the value of fixated options, which is essential for decision making. Yet as a decision unfolds, it remains unclear how prefrontal regions determine which option should be fixated next. Here we show that anterior cingulate cortex (ACC) encodes the value of options in the periphery to guide subsequent fixations during economic choice. In an economic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 55 publications
5
11
0
Order By: Relevance
“…Our main findings suggest extensions to theoretical accounts of the overarching function of the ACC for adaptive behavior. First, the finding of prolonged information sampling after ACC-TUS supports recent electrophysiological and imaging studies showing that activity in the ACC predicts information sampling of visual objects and attention to maximize reward outcomes [17,18,25,42]. However, we found a functional deficit of information sampling only in the gain-loss learning context in which subjects expected lower payoff, suggesting that the ACC contributes to information sampling, particularly in motivationally challenging conditions.…”
Section: Extending Existing Functional Accounts Of Acc Functionssupporting
confidence: 88%
See 4 more Smart Citations
“…Our main findings suggest extensions to theoretical accounts of the overarching function of the ACC for adaptive behavior. First, the finding of prolonged information sampling after ACC-TUS supports recent electrophysiological and imaging studies showing that activity in the ACC predicts information sampling of visual objects and attention to maximize reward outcomes [17,18,25,42]. However, we found a functional deficit of information sampling only in the gain-loss learning context in which subjects expected lower payoff, suggesting that the ACC contributes to information sampling, particularly in motivationally challenging conditions.…”
Section: Extending Existing Functional Accounts Of Acc Functionssupporting
confidence: 88%
“…These studies found that neurons in the ACC encoded the pre-learned value of objects when they were fixated [18] or peripherally attended [16,19]. Moreover, subpopulations of ACC neurons also encode the value of objects that are not yet fixated but are possible future targets for fixations [17]. Disrupting these signals with TUS in our study is a plausible reason causing uncertainty about the value of objects and for prolonging information sampling durations.…”
Section: Acc Modulates the Efficiency Of Information Samplingsupporting
confidence: 48%
See 3 more Smart Citations